2021
DOI: 10.1021/acs.organomet.1c00086
|View full text |Cite
|
Sign up to set email alerts
|

Oxo 2-Adamantylidene Complexes of Mo(VI) and W(VI)

Abstract: Molybdenum and tungsten oxo 2-adamantylidene (Adene) complexes that contain two nonafluoro-tert-butoxide (ORF9) ligands have been prepared through addition of 2-methylene- or 2-ethylideneadamantane to neophylidene or neopentylidene complexes. The isolated oxo complexes include W­(O)­(Adene)­(ORF9)2(PPh2Me) (1 W ), W­(O)­(Adene)­(ORF9)2 (2 W ), W­(O)­(Adene)­(2,5-dimethylpyrrolide)2 (3 W ), W­(O)­(Adene)­(2,5-dimethylpyrrolide)­(2,6-dimesitylphenoxide) (4 W ), Mo­(O)­(Adene)­(ORF9)2(PPhMe2) (1 Mo ), and Mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…In the subsequent years, the Schrock group reported other tungsten oxo alkylidenes and the role of ancillary ligands on the catalytic activity and product selectivity were deeply discussed (i.e. 15 and 16) [36][37][38][39][40][41][42]. Moreover, Buchmeiser and co-workers synthetized a series of very active cationic tungsten oxo alkoxy alkylidene bearing an N-heterocyclic carbene (NHC) as fourth ligand (17)(18) [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the subsequent years, the Schrock group reported other tungsten oxo alkylidenes and the role of ancillary ligands on the catalytic activity and product selectivity were deeply discussed (i.e. 15 and 16) [36][37][38][39][40][41][42]. Moreover, Buchmeiser and co-workers synthetized a series of very active cationic tungsten oxo alkoxy alkylidene bearing an N-heterocyclic carbene (NHC) as fourth ligand (17)(18) [43][44][45].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge acquired on tungsten oxo alkylidenes allowed the synthesis of molybdenum and vanadium oxo analogues as well as other molybdenum precursors that are also active in metathesis (22,23) [40,[52][53][54][55][56][57][58]. The number of existing molybdenum oxo alkylidenes is limited and their activity for olefin metathesis is usually lower than that of tungsten species.…”
Section: Introductionmentioning
confidence: 99%
“…[25 -27] However, recent synthetic developments in molecular chemistry have shown that W oxo adamantylidene complexes can be readily prepared (Scheme 1,c), possibly as a consequence of the sterically demanding adamantylidene, which prevents decomposition by homocoupling. [28] In this work, we investigate the grafting and reactivity of W-oxo adamantylidenes containing strongly donating X/Y ligands (pyrrolidine) 1 and weakly donating X/Y ligands (-OR F9 ) 2 (Scheme 1,c). We show that both species can be grafted to silica, with the activity of the grafted species following the established trends of activity with electron donation from the ligands.…”
Section: Introductionmentioning
confidence: 99%
“…Most such investigations have been performed on the larger family of imido complexes, [16,24] because isolable oxo complexes have been more difficult to prepare ( Scheme 1 ,b ) [25–27] . However, recent synthetic developments in molecular chemistry have shown that W oxo adamantylidene complexes can be readily prepared ( Scheme 1 ,c ), possibly as a consequence of the sterically demanding adamantylidene, which prevents decomposition by homocoupling [28] . In this work, we investigate the grafting and reactivity of W‐oxo adamantylidenes containing strongly donating X/Y ligands (pyrrolidine) 1 and weakly donating X/Y ligands (‐OR F9 ) 2 ( Scheme 1 ,c ).…”
Section: Introductionmentioning
confidence: 99%
“…In the early 1980s, Schrock et al developed tungsten oxo alkylidene complexes, which were among the first well-defined high oxidation state complexes for olefin metathesis reactions. , The focus soon shifted to tungsten and molybdenum imido alkylidene complexes. Recently, molybdenum oxo alkylidene complexes were added to the arsenal of olefin metathesis catalysts. While the imido ligand in molybdenum and tungsten imido alkylidene complexes allows for a broad range of variations, the variability in the corresponding molybdenum and tungsten oxo alkylidene complexes is intrinsically lower. So far, reports on olefin metathesis-active tungsten alkylidene complexes with other ligands than oxo or imido ligands are scarce. …”
Section: Introductionmentioning
confidence: 99%